2017
DOI: 10.14198/ingeo2017.67.08
|View full text |Cite
|
Sign up to set email alerts
|

Propuesta de creación de una microrreserva en el Peñón de Salobreña para la protección de los hábitats del litoral de Granada (España)

Abstract: Este trabajo se publica bajo una licencia de Creative Commons Reconocimiento-NoComercial 4.0 Internacional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…As regards P. pinaster , it has been confirmed that it grew naturally in certain enclaves in the Serranía de Ronda, such as the Sierra Bermeja (Gómez-Zotano, 2004; Olmedo-Cobo et al, 2019a, 2019b). In 1752 the Marqués de la Ensenada Land Survey referred to the peridotite outcrops as “barren land by nature which produces nothing,” with the exception of the places that hosted a population of “ pinos bravíos ” (the adjective “bravíos” refers to wild pines, i.e.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…As regards P. pinaster , it has been confirmed that it grew naturally in certain enclaves in the Serranía de Ronda, such as the Sierra Bermeja (Gómez-Zotano, 2004; Olmedo-Cobo et al, 2019a, 2019b). In 1752 the Marqués de la Ensenada Land Survey referred to the peridotite outcrops as “barren land by nature which produces nothing,” with the exception of the places that hosted a population of “ pinos bravíos ” (the adjective “bravíos” refers to wild pines, i.e.…”
Section: Resultsmentioning
confidence: 93%
“…A detailed study of these sources revealed that the landscape was dominated by conifer and broadleaf forests. As regards the most unusual formations in ecological and landscape terms, which include the A. pinsapo , Spanish fir forests, the earliest references appear in the 17th century in various municipal ordinances and in inventories of wood used to supply the Spanish Navy or for building houses (see Becerra, 2006; Gil, 2002; Gómez-Zotano, 2004, 2006; Gómez-Zotano and Olmedo-Cobo, 2021). The information about the Spanish fir in the General and Specific Questions from the Ensenada Land Survey, from the mid-18th century (Gómez-Zotano and Olmedo-Cobo, 2021) is also of great interest, as are the written accounts of travelers and naturalists gathered by Guzmán et al (2013) and López-Quintanilla (2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For these reasons, questions concerning the interaction of the mycorrhizae with these shrubby species should be investigated as well as their effects on the different vegetational structures that these species constitute. (Sánchez et al 2008;Gómez-Zotano et al 2017) (Brullo et al 2008), or of the Artemision arborescentis alliance, Lycio intricati-Salsoletum oppositifoliae association (Brullo et al 2013), especially in the coasts of southern Sicily and in southern Spain.…”
Section: Discussionmentioning
confidence: 99%